The Relationship between Foreign Tourists and Average Length of Stay on Local Original Income (PAD) in Bali Province with Tourist Expenditure as an Intervening Variable - Ariani, Chindy; Wahed, Mohammad (Journal of Regional Economics and Development, 2026)
This study aims to determine the direct and indirect relationship between the variables of the number of foreign tourist visits and the average length of stay on Regional Original Income through foreign tourist expenditure as an intervening variable through a path analysis approach. This study uses secondary data from the Central Statistics Agency and the Bali Provincial Tourism Office for the period 2000-2024. The results show that the number of foreign tourist visits and foreign tourist expenditure have a significant positive relationship to Regional Original Income in Bali Province, while the average length of stay has a significant negative relationship to Regional Original Income. In addition, foreign tourist expenditure acts as an intervening variable that positively mediates the relationship between the number of foreign tourist visits and Regional Original Income, and negatively mediates the relationship between the average length of stay and Regional Original Income.